Knowing Women Same-Sex Intimacy, Gender, and Identity in Postcolonial Ghana - Owusua Dankwa, Serena (Social Sciences, 2021)
This intimate study focuses on the everyday lives of working-class women who love women in Ghana. Set in the context of the political, economic and social developments affecting people's lives across Africa, it goes beyond LGBT rights by including desires and intimacies not captured in categories of sexual identity.